Chennakeshava temple, Beluru, Sculptures depicting lifestyle of citizens, p28 - Brig Ajai Singh (2021)
Image courtesy: Brig A.P. Singh - www.collectingmoments.in ; Image courtesy: Brig AP Singh - www.collectingmoments.in